Pendampingan Aparatur Pemerintahan Desa dalam Penggunaan Aplikasi Sigap di Desa Along dan Mutiara - Anata S, Yudha; Afra, Raisatul; Afrijal (LSM Catimore dan Sahabat, 2026)
This community service activity aimed to enhance the capacity of village officials in managing gampong data through the SIGAP (Sistem Informasi Gampong) application in Along and Mutiara Villages, Salang District, Simeulue Regency. Key challenges included low digital literacy, unstructured data management, and irregular data updates. The program consisted of a three-day training session followed by 45 days of intensive technical assistance. The training focused on introducing SIGAP features, managing population data, village profiles, and administrative services. The results showed significant improvements in officials’ knowledge and technical skills, enabling independent data input and updates. The optimized use of SIGAP improved administrative efficiency, data accuracy, and public service delivery at the village level, emphasizing the importance of continuous assistance for successful digital governance in rural areas.